P39 Cross sectional survey of medical student volunteering and education during the coronavirus pandemic in the United Kingdom. (8th April 2021) - ,; Byrne, Matthew H V; Ashcroft, James; Alexander, Laith; Wan, Jonathan; Harvey, Anna; Clelland, Andrew; Schindler, Nick; Brassett, Cecilia; ,; Vance, Gillian; Burford, Bryan; et al.
Abstract: Introduction: COVID-19 led to global disruption of healthcare and many students volunteered to provide clinical support. Volunteering to work was a unique medical education opportunity; however, it is unknown whether this was a positive learning experience. Methods: The COVID Ready 2 study is a national cross-sectional study of all medical students at UK medical schools. We will compare opinions of those who did and did not volunteer to determine the educational benefit and issues they faced. We will use thematic analysis to identify themes in qualitative responses, in addition to quantitative analysis. Results: The primary objective is to explore the effect of volunteering during the pandemic on medical education in comparison to those who did not volunteer. Our secondary objectives are to identify: whether students would be willing to assume similar roles in a non-pandemic setting; if students found the experience more or less beneficial than traditional hospital placements and reasons for this; what the perceived benefits and disadvantages of volunteering were; the difference in perceived preparedness between students who did and did not volunteer for foundation training year one and the next academic year; training received by volunteers; and to explore issues associated with volunteering, including safety issues and issues with role and competence. Conclusions: We anticipate this study will help identify volunteer structures that have been beneficial for students, so that similar infrastructures can be used in the future; and help determine whether formal voluntary roles should be introduced into the non-pandemic medical curriculum.